Heavy metal and health risk assessment of paragis (Eleusine indica) grass concoction from different parts of Laguna near the Laguna Lake shore line - Gawat, Mariero H.; Martinez, Danielle Theo L. (2019)
Paragis (Eleusine indica) grass is in the Philippines has become popular as herbal medicine, claimed to cure several medical conditions when processed and consumed as a concoction. In this study, concentration of three heavy metals namely, Lead (Pb), Cadmium (Cd), and Chromium (Cr) in Par- agis grass concoction from the three towns (Los Baños, Bay, and Calamba) along Laguna Lake were determined. The health-risk effects, specifically non-carcinogenic, due to the exposure of the three heavy metal studied for adult consumers were estimated. Heavy metal analysis were carried out through Flame Atomic Absorption Spectrophotometry (AAS). Results show that the highest con- centrations of Pb, Cd, and Cr were found to be from the samples gathered in Bay, Laguna. Also, for the Estimated Daily Intake of Pb, Cd, and Cr, Paragis grass concoction from Bay, Laguna exceeds the maximum permissible limit set by Food and Agriculture Organizations (FAO). For the non-car- cinogenic risks associated with the consumption of the samples, estimated Target Hazard Quotient (THQ) for the three samples, for Pb, Cd and Cr did not exceed the limit (THQ>1). In the estimation of the the potential health risk posed by more than one metal, the computed Hazard Index (HI) is less than one, thus no adverse health effects are expected because of exposure for Pb. Cd and Cr, and the risk of the person getting a disease from exposure to the sample is low.
Keywords: Herbal medicine